Sosialisasi Pemilu Serentak kepada Pemilih Pemula di Kabupaten Merangin - Salman; Farda, Lina (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
The 2024 simultaneous elections are an important momentum in Indonesian democracy, involving all elements of society, including first-time voters. First-time voters in Merangin Regency tend to lack understanding of the stages and process of the election, which can lead to low political participation. For this reason, socialization was carried out through the distribution of pamphlets which aimed to provide a basic understanding of simultaneous elections, the stages involved, as well as the rights and obligations of voters. This approach focuses not only on providing information, but also on building a deeper political awareness, so that novice voters can understand how important their right to vote is. By increasing this understanding, it is hoped that novice voters will be more active in participating and voting wisely, so that they can make a positive contribution to the quality of elections and the future of the nation.